2005
DOI: 10.1111/j.1550-7408.2005.00048x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Localization of a Protein Immunologically Related to Caltractin (Centrin) in the Myonemes and Membranelles of the Heterotrich Ciliate Stentor coeruleus

Abstract: The contractile properties of the myonemes of Stentor are very similar to caltractin (centrin)-containing fibers of other organisms. We investigated whether the calcium-binding protein caltractin was present in Stentor by using three different antibodies to caltractin or caltractin-related proteins, in conjunction with immunofluorescence microscopy and protein blotting. Immunofluorescence demonstrated that a protein immunologically similar to caltractin is present in the myonemes and in the bases of the membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Later investigations in other protozoan organisms revealed centrin as an important component of contractile structures widely found in protists. Besides the striated flagella/cilia rootlets (Guerra et al 2003;Lemullois et al 2004), centrin is also found present in the myonemes of ciliate Eudiplodinium maggii (Vigues 1994), Vorticella microstoma (Levy et al 1996), and Stentor coeruleus (Maloney et al 2005); the infraciliary lattice of Parmecium (Allen et al 1998); the cytopharyngeal apparatus of the ciliates Nassula and Furgasonia (Vigues et al 1999); the rhizoplast in Platymonas subcordiformis (Salisbury and Floyd 1978); the nuclear basal body connectors and interbasal body distal fibers in Chlamydomonas reinhardtii (Salisbury et al 1988;Sanders and Salisbury 1989); and the basal rings in Toxoplasma gondii (Hu 2008). These contractile structures are highly divergent in their appearance and function in various cellular processes including flagellar beat (Melkonian 1980), response to external stimuli (Febvre 1981), food ingestion (Tucker 1968), organelle positioning and segregation (Wright et al 1985(Wright et al , 1989, and cell cycle-dependent arrangement of the cytoskeleton (Hu 2008).…”
Section: Centrins On Contractile Structuresmentioning
confidence: 99%
“…Later investigations in other protozoan organisms revealed centrin as an important component of contractile structures widely found in protists. Besides the striated flagella/cilia rootlets (Guerra et al 2003;Lemullois et al 2004), centrin is also found present in the myonemes of ciliate Eudiplodinium maggii (Vigues 1994), Vorticella microstoma (Levy et al 1996), and Stentor coeruleus (Maloney et al 2005); the infraciliary lattice of Parmecium (Allen et al 1998); the cytopharyngeal apparatus of the ciliates Nassula and Furgasonia (Vigues et al 1999); the rhizoplast in Platymonas subcordiformis (Salisbury and Floyd 1978); the nuclear basal body connectors and interbasal body distal fibers in Chlamydomonas reinhardtii (Salisbury et al 1988;Sanders and Salisbury 1989); and the basal rings in Toxoplasma gondii (Hu 2008). These contractile structures are highly divergent in their appearance and function in various cellular processes including flagellar beat (Melkonian 1980), response to external stimuli (Febvre 1981), food ingestion (Tucker 1968), organelle positioning and segregation (Wright et al 1985(Wright et al , 1989, and cell cycle-dependent arrangement of the cytoskeleton (Hu 2008).…”
Section: Centrins On Contractile Structuresmentioning
confidence: 99%
“…The OA is dominated structure on the anterior end of the cell, consisting of thousands of centrioles and cilia [7] organized into a ciliated band of membranelles. The membranellar band encircles the broad end of the cell body and terminates inside the buccal cavity or gullet [8,9]. However, the protein constituents of OA and their spatiotemporal expression patterns in OA regeneration are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…From these results, it is likely that KI treatment is inhibiting additional cellular processes beyond myoneme contraction, or that KI is generally cytotoxic to Stentor . Nevertheless, it was worthwhile to test the effects of KI treatment on the immediate wound repair response, as currently no suitable alternative is known to robustly inhibit myoneme contraction without significantly affecting cilia function, and the composition of the myonemes is not yet fully identified [22, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Myonemes, located immediately under the KM fibers, are contractile fibers responsible for the rapid contraction of the cell from an extended trumpet shape to a sphere at rates up to 10 – 20 cm/s [20], [21]. Immunostaining of Stentor showed the localization of a protein that is immunologically related to centrin/caltractin, a class of EF-hand calcium binding proteins that form contractile filaments in a variety of organisms, in myonemes [22]. Further details on the anatomy of Stentor can be found in previous work [23].…”
Section: Introductionmentioning
confidence: 99%